Sustainable procurement in the RMG sector of Bangladesh: a focus on ethical practices & environmental impact - Islam, Md. Fakhrul (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.